Early Loss of Fat Mass During Chemoradiotherapy Predicts Overall Survival in Locally Advanced Squamous Cell Carcinoma of the Lung, but Not in Locally Advanced Squamous Cell Carcinoma of the Head and Neck - Willemsen, A. C. H.; Degens, J. H. R. J.; Baijens, L. W. J.; Dingemans, A-M. C.; Hoeben, A.; Hoebers, F. J. P.; De Ruysscher, D. K. M.; Schols, A. M. W. J. (Frontiers in Nutrition, 2020)
Background: Cancer cachexia is highly prevalent in advanced non-small cell lung cancer (NSCLC) and locally advanced head and neck squamous cell carcinoma (LAHNSCC), and compromises treatment tolerance and overall survival (OS). NSCLC and LAHNSCC patients share similar risk factors, and receive comparable anti-cancer treatment regimens. The aim of this study was to determine the predictive value of body composition assessed by bioelectrical impedance analysis (BIA) and handgrip strength (HGS) (baseline and early changes during therapy) on OS in NSCLC and LAHNSCC patients treated with platinum-based chemoradiotherapy (CRT) or cetuximab-based bioradiotherapy (BRT). To elucidate potential underlying determinants of early changes in body composition and HGS, specific (fat and fat free) mass loss patterns of squamous NSCLC (sNSCLC) were compared to human papilloma virus negative (HPV-) LAHNSCC patients treated with CRT. Methods: Between 2013-2016, BIA and HGS were performed at baseline and after three weeks of CRT/BRT in LAHNSCC and NSCLC patients treated with curative intent. Results: Two hundred thirty-three patients were included for baseline measurements. Fat free mass index (FFMI) and HGS<10th percentile of reference values at baseline were both prognostic for poor OS in NSCLC and LAHNSCC (HR 1.64 [95%CI 1.13-2.39], p= .01 and HR 2.30 [95%CI 1.33-3.97], p=.003 respectively), independent of Charlson Comorbidity Index, cancer site, and gross tumor volume. Early fat mass (FM) loss during CRT was predictive for poor OS in sNSCLC (n=64) (HR 3.80 [95%CI 1.79-8.06] p=<.001) but not in HPV- LAHNSCC (n=61). In patients with significant weight loss (>2%) in the first three weeks of CRT (sNSCLC n=24, HPV- LAHNSCC n=23), the FM change was -1.4 ± 14.5% and -8.7 ± 9.0% in sNSCLC and HPV- LAHNSCC patients respectively (p<.05). Fat fee mass change was -5.6 ± 6.3% and -4.0 ± 4.3% for sNSCLC and HPV- LAHNSCC respectively (p=.31). Conclusion: FFMI and HGS<10th percentile at baseline are independent prognostic factors for poor OS in NSCLC and LAHNSCC patients treated with CRT/BRT. The specific composition of mass loss during first three weeks of CRT significantly differs between sNSCLC and HPV- LAHNSCC patients. Early FM loss was prognostic in sNSCLC only.